Transcriptome-based WGCNA reveals the molecular regulation of xylem plasticity in acclimation to drought and rewatering in mulberry - Tian, Yue; Zhai, Zeyang; Yang, Yujie; Zhang, Kaixin; Ma, Sang; Cheng, Jialing; Liu, Li; Cao, Xu (Frontiers in Plant Science, 2024)
Xylem plasticity is important for trees to coordinate hydraulic efficiency and safety under changing soil water availability. However, the physiological and transcriptional regulations of cambium on xylem plasticity are not well understood. In this study, mulberry saplings of drought-resistant Wubu and drought-susceptible Zhongshen1 were subjected to moderate or severe drought stresses for 21 days and subsequently rewatered for 12 days. The anatomical, physiological and transcriptional responses in wood and cambium were analyzed. Most parameters were not affected significantly under moderate drought for both cultivars. Severe drought led to decreased vessel lumen diameter and increased vessel frequency, increased starch and hemicellulose in wood of both cultivars. Notably, increased soluble sugars and lignin were detected only in wood of Wubu. In cambial zone, levels of starch, glucose, fructose, mannose and cytokinin were decreased in both cultivars, whereas soluble sugars were increased in Wubu but deceased in Zhongshen1. RNA-sequencing identified 1824 and 2471 differentially expressed genes in Wubu and Zhongshen1 under severe drought, respectively. These responses were partially recovered after rewatering. Weighted gene correlation network analysis identified modules of co-expressed genes correlated with the anatomical and physiological traits of wood and cambium, with the turquoise and green modules most strongly correlated with traits under drought or rewatering. These modules were enriched in gene ontology terms related to cell division, cytoskeleton organization, cell wall modification, dark respiration, vesicle transport and protein metabolism. Detailed gene expression patterns indicate that reprogramming of cambium activity was relatively similar in both cultivars, but at different scales. These findings provide important insights into the physiological and molecular mechanisms underlying xylem plasticity based on cambium and offer valuable references for breeding drought-resistant mulberry and other woody species in light of future drier climate scenarios.